2011
DOI: 10.1016/j.rinphs.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized ethosomes bearing ketoprofen for improved transdermal delivery

Abstract: The potential of ethosomes for delivering ketoprofen via skin was evaluated. The ethosomes were prepared, optimized and characterized. Vesicular shape, size and entrapment efficiency were determined by transmission electron microscopy, dynamic light scattering and minicolumn centrifugation technique, respectively. Vesicle sizes varied from 120.3±6.1 to 410.2±21.8 nm depending on the concentrations of soya phosphatidyl choline (SPC) and ethanol. Entrapment efficiency increased with concentrations of SPC and eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
72
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 35 publications
9
72
1
2
Order By: Relevance
“…This is also in accordance with previous findings of Chourasia et al, 2011. [19] HA drug solution released most of the drug within 2-4 h. Cumulative amount of drug permeated per unit area versus time graph was plotted and transdermal flux (J) was calculated from the slope of linear portion [ Figure 2a]. On the analysis of transdermal flux of the same formulations, it was found that results followed the similar pattern as that of cumulative percent drug release [ Figure 2b] which varied from 66.69163.5 µg/cm 2 /h (conventional gel) to 163.5 µg/cm 2 /h (GEL F12).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…This is also in accordance with previous findings of Chourasia et al, 2011. [19] HA drug solution released most of the drug within 2-4 h. Cumulative amount of drug permeated per unit area versus time graph was plotted and transdermal flux (J) was calculated from the slope of linear portion [ Figure 2a]. On the analysis of transdermal flux of the same formulations, it was found that results followed the similar pattern as that of cumulative percent drug release [ Figure 2b] which varied from 66.69163.5 µg/cm 2 /h (conventional gel) to 163.5 µg/cm 2 /h (GEL F12).…”
Section: Resultssupporting
confidence: 94%
“…This observation supports the findings, of [18,19] which state that higher concentration of ethanol is responsible for decrease in the size of vesicle as it furnish a surface negative net charge to the vesicular systems by altering some surface characteristics.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Chan et al [65] developed nanosized ethosomes bearing ketoprofen for improved transdermal delivery. Ethosomal vesicles were prepared by the method reported elsewhere with some modifications.…”
Section: Phospholipidsmentioning
confidence: 99%
“…6,92 A preclinical study testing the efficacy of ketoprofen in ethosomes for transdermal drug delivery was recently published. 93 Improved drug permeation across human skin and higher transdermal flux with ethosomal formulations compared to hydroethanolic drug solution was revealed in vitro. Based on transdermal flux, the estimated steady state in vivo plasma concentration from ethosomes attained therapeutic drug levels, whereas the hydroethanolic drug solution exhibited subtherapeutic drug concentrations with a patch size of 50 cm 2 .…”
mentioning
confidence: 99%